Pengaruh Kepemimpinan Transformasional Pada Sinisisme terhadap Perubahan Organisasional dengan Keadilan Distributif sebagai Pemoderasi - Mega Asri Zona (Management Insight: Jurnal Ilmiah Manajemen, 2014)
This research used transformational leadership as independent variables which had negative influence on cynicism about organizational change. While distributive justice used as moderated variable that expected to affect the relationship of transformational leadership on cynicism about organizational change. The survey was conducted to 250 employees of PT PLN branch Padang (Rayon Kuranji, Rayon Tabing, Rayon Belanti and Rayon Indarung), PT Telkom area Padang, PT MNC Sky Vision (KPP KPP Padang and Bukittinggi). At least, 202 Questionnaires were collected, but only 187 questionnaires that can be processed.